Product value analysis of processed kimpul products as an effort to develop local resources - Endang Retno Wedowati; Fungki Sri Rejeki; Diana Puspitasari (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2022)
Kimpul (Xanthosoma sagittifolium) is one of the local products that produce non-rice carbohydrates that have the potential to be developed. The potential of kimpul tubers can be developed by utilizing it into various types of processed products to provide value. The kimpul tubers can be processed into kimpul chips, kimpul sticks, or other preparations. Meanwhile, kimpul flour can be processed into various products, including wet noodles, biscuits, cookies, pastries, or other processed forms. From the various diversification of processed products, it has the potential to be developed into food industry products. For this reason, it is necessary to analyze the value of the various preparations in terms of product performance and required production costs. The purpose of this study was to determine the performance of various kimpul preparations with various criteria, analyze the production costs of various kimpul preparations, conduct value analysis of various kimpul preparations based on performance and cost analysis, and provide recommendations for the type of product that is able to provide the best value. Product performance is based on the parameters of organoleptic properties, product attractiveness, product benefits, and product purchase decisions. The value of the product is analyzed based on the benefits of the product and the costs required to realize these benefits. The results of product value analysis show that products that have high benefits, but only require relatively low costs provide high product values. Alternative products that are recommended to be produced are kimpul chips, kimpul sticks, and kimpul cookies.